Kinetics of the serological response up to one year after tularemia - Lindgren, Helena; Eklund, Johan; Eneslätt, Kjell; Sjöstedt, Anders (Frontiers in Cellular and Infection Microbiology, 2023)
F. tularensis-specific IgM and IgG antibody titers were determined by an LPS-based ELISA assay on five occasions one to twelve months after onset of ulceroglandular tularemia in 19 individuals. Peak IgM antibody titers were observed at the one-month time point and peak IgG antibody titers at the two-month time point. Both IgG and IgM antibody levels declined linearly thereafter with rather similar kinetics. Compared to the average one-month antibody titers, average IgG titers were not significantly lower before the 12-month time point and IgM titers before the 4-month time point. All, but one average titer, were significantly increased compared to the cut-off of the assay. Average IgG and IgM titers were significantly lower for the group ≥ 69 years old compared to the group < 69 years. Collectively, the data demonstrate a persistence of F. tularensis-specific IgM and IgG antibody titers for at least 12 months after ulceroglandular tularemia. Thus, low, but significantly elevated F. tularensis-specific antibody titers are of limited diagnostic value since they are not indicative of acute disease.